2019
DOI: 10.1016/j.ssmph.2019.100482
|View full text |Cite|
|
Sign up to set email alerts
|

Pre-acculturation as a risk factor for obesity: Findings from the Health of Philippine Emigrants Study (HoPES)

Abstract: Immigrants to the United States may have an advantage in terms of healthier weight, but tend to gain excessive weight after arrival, and may suffer from obesity and related health conditions. Acculturation theory suggests that this increase in obesity risk is due to adoption of unhealthy western dietary behaviors, and assumes that “eastern/traditional” dietary behaviors prior to migration are healthier. While this assumption is supported by studies conducted several decades ago, the phenomenon of globalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The study found that immigrants to the USA tended to be healthier upon arrival than their native-born counterparts, but that their health deteriorated with time. Additional analyses of the HoPES data suggest that pre-acculturation (the process by which one becomes familiar with the culture of a country before moving to it) may be a risk factor for obesity in Philippine migrants to the USA [89]. Pre-acculturation was associated with increases in BMI, waist circumference, and waist to height ratio.…”
Section: Obesity Among Philippine Immigrants In the Usamentioning
confidence: 91%
“…The study found that immigrants to the USA tended to be healthier upon arrival than their native-born counterparts, but that their health deteriorated with time. Additional analyses of the HoPES data suggest that pre-acculturation (the process by which one becomes familiar with the culture of a country before moving to it) may be a risk factor for obesity in Philippine migrants to the USA [89]. Pre-acculturation was associated with increases in BMI, waist circumference, and waist to height ratio.…”
Section: Obesity Among Philippine Immigrants In the Usamentioning
confidence: 91%
“…One recent review found that among Latinx and South Asians in the United States (US), longer length of residence in the US was associated with greater cardiovascular risk and mortality across several studies [3]. Research has begun to link acculturation with metabolic abnormalities known to increase risk for cardiovascular disease, such as higher body mass index [4,5], abdominal obesity [6,7], and type II diabetes [8,9]. However, fewer studies have examined this association using biomarkers of metabolic abnormalities such as lipid, cholesterol, and glucose levels in the blood that provide more objective measurement of arteriosclerosis risk and type II diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Asian Americans are a group of considerable heterogeneity, composed of people who come from approximately 19 regions across East Asia, Southeast Asia, and the Indian subcontinent with varying socioeconomic statuses and proportions foreign born (Pew Research Center 2019). Furthermore, the existence of remote acculturation (Ferguson and Bornstein 2012) or pre-acculturation (Gee et al 2019), fueled by globalization, signals that the extent to which migrating Asians are already exposed to U.S. culture may vary across these regions. Thus, a larger sample is needed for future research in order to better understand how acculturation is associated with self-rated health among such various Asian ethnic groups.…”
Section: Discussionmentioning
confidence: 99%